An integrated web-based decision support system for tendering processes - Mohamad Noor, Noor Maizura (Fakulti Sains dan Teknologi, 2010)
Contemporary managers are making critical technical and business decisions to improve their organisational processes, and decision-making is a central managerial activity. It remains an immensely challenging role of managers in any organisation. Decision-making in tendering processes is one such crucial task in any public enterprise. A Decision Support System (DSS) is an interactive computer-based system that helps decision makers (DMs) utilise data and models to solve complex and unstructured problems. Procurement or the tendering process is a decision problem of paramount importance for any business. A critical and vital procurement task is to select the best contractor during the tendering or bidding process. A case study is drawn from the construction business in order to demonstrate the applicability of our approach.